Pembangunan Sistem Pengelolaan Aset pada PT. Indonesia Power Suralaya Berbasis Web - Savira Sulistyo; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia Power Suralaya is one of the subsidiary company of PT PLN (Persero) located in Cilegon City, Banten Province. PT. Indonesia Power Suralaya has six divisions, namely Finance, Public Relations, Administration, Information Systems (SIS) 1-4 Unit, and 5-7 Unit. Division of SIS has problems in asset management of asset data collection, borrowing goods, returning goods, and treatment goods. Division of SIS is using Microsoft Excel to asset data collection. Division of SIS has difficulties in monitoring of incoming goods and outgoing goods. Division of SIS has constraints in searching for users of previous items because data management of borrowing goods and returning goods is still done by writing on a notebook. Division of SIS hasn't provided data management to treatment of goods. PT Indonesia Power Suralaya allows employees to borrow goods. Employees have difficulties in status monitoring of borrowing goods and returning goods in office. This research has developed an asset management system to overcome these problems. This system uses web technology that allows the system to be accessed easily by using the web browser. This system is expected to help PT. Indonesia Power Suralaya in asset management. This research was using Object Oriented Analysis and Design (OOAD) method and Object Oriented Programming (OOP) method for developing an asset management system. This system has been tested using white box testing for unit testing and integration testing and also using black box testing for validation testing.